Barriers to Quran Reading Instruction at MA Hasanuddin Blitar: Hambatan dalam Pengajaran Pembacaan Al-Quran di MA Hasanuddin Blitar - Faizah, Ulfa Auliatul; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The ability to read the Quran correctly is a fundamental aspect of Islamic education that contributes to students’ spiritual development and religious identity. Specific background: Despite its importance, many students in Islamic schools still face challenges in mastering Quranic reading skills, particularly in applying Tajwid and Makhraj rules. Knowledge gap: Previous studies have highlighted Quran literacy problems in various contexts, but limited research has systematically analyzed the underlying barriers in senior high-level Islamic institutions. Aims: This study aims to identify and analyze the factors hindering Quran reading instruction at MA Hasanuddin Gaprang, Blitar Regency. Methods: Using a qualitative descriptive approach, data were collected through observation and interviews with students and teachers. Results: The findings reveal several obstacles, including decreased student motivation, insufficient school facilities, and the continued use of outdated teaching methods, leading to disengagement in learning. Novelty: Unlike earlier research focusing on student performance alone, this study emphasizes the interplay between internal (motivation, background, intelligence) and external (school facilities, teaching methods) factors in shaping learning outcomes. Implications: The study provides practical recommendations for improving Quran reading pedagogy, serving as a reference for educators and policymakers to enhance the quality of Islamic education.Highlights: Identifies internal and external obstacles in Quran reading. Emphasizes the need for improved teaching methods. Highlights the importance of facilities in supporting learning. Keywords: Quran Reading, Learning Barriers, Motivation, Teaching Methods, Islamic Education